Symultaniczno-Sekwencyjna Nauka Czytania® na wczesnym etapie edukacyjnym w kontekście roli umiejętności czytania w rozwoju człowieka - Orłowska-Popek, Zdzisława; Bielenda-Mazur, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
In this article, the authors present a reading technique addressed to pre-school and earlyschool children in the context of the role of reading skills in human development. The authors of the paper describe the technique of teaching reading and the neurobiological basis of this technique, dedicated to children with and without developmental disorders.